PENGINDERAAN JAUH UNTUK KAJIAN PESISIR - Nurul Ihsan Fawzi; Marindah Yulia Iswari (OSEANA, 2018)
REMOTE SENSING FOR COASTAL STUDIES. Coastal ecosystem is an ecological system that is important and the most productive area on earth. On the other hand, pressure on coastal ecosystems for human necessity cause decrease quality of coastal ecosystems. Utilization of coastal areas requires the proper management and suitable with objective. Good management requires appropriate information for decisionmaking. For spatial data, acquisition of information through remote sensing data is the best option. This paper will discuss the utilization of using remote sensing for coastal analysis. Coastal management requires information accurately and quickly to follow up issues or problems that growth up. Remote sensing has provided the capability to provide that information by translating information from digital number to thematic information. Regardless from the problem existing mapping method, utilization remote sensing in the future will be the main data on coastal management, especially in the monitoring and measurement of biophysical parameter in coastal areas.